Viability of Symbiodinium dispersed by the stoplight parrotfish Sparisoma viride (2017)
Herbivorous fishes produce profound effects on the coral reef dynamics and represent a major role as resilience drivers. The finding of viable Symbiodinium cells in the stoplight parrotfish Sparisoma viride faeces supports the notion of these fishes as vectors of a free-living Symbiodinium (FLS) reservoir. However, the magnitude and potential effect of the zooxanthellae dispersed by S. viride was until now unknown. Thus, the purpose of this study was to estimate the FLS viable cells dispersal capacity by S. viride faeces through reefs. We aimed to quantify the number of viable vs. dead cells according to the size faeces pellets. Using a standardized protocol of flow cytometry, we found that to 23,12%±1,50 of the total zooxanthellae are viable in S. viride faeces. Moreover, there are resilience consequences related to S. viride FLS endozoochory evident with the constant input of viable symbiotic zooxanthellae in reefs. All fecal depositions analyzed contained a significant viable cells presence...